2015
DOI: 10.1039/c5tb01435b
|View full text |Cite
|
Sign up to set email alerts
|

Designed nucleus penetrating thymine-capped dendrimers: a potential vehicle for intramuscular gene transfection

Abstract: A nucleus penetrating vehicle is indispensible when seeking to deliver plasmid DNA for gene transfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Of the tested thymine coverages, only the 50% thymine-modified PAMAM promoted both siRNA/pDNA condensation and efficient release of siRNA/pDNA, which is predictive of increased transfection activity. This finding is consistent with previous studies suggesting enhanced gene transfection mediated by the 50% thymine-capped PAMAM dendrimer/pDNA complex (17). Thus, 50% thymine-capped PAMAM dendrimers were used to form the dendrimer/siRNA/pDNA complex at a weight ratio of approximately 2:1:1.…”
Section: Preparation and Characterization Of Tumor-targeted Lipid/ De...supporting
confidence: 92%
See 1 more Smart Citation
“…Of the tested thymine coverages, only the 50% thymine-modified PAMAM promoted both siRNA/pDNA condensation and efficient release of siRNA/pDNA, which is predictive of increased transfection activity. This finding is consistent with previous studies suggesting enhanced gene transfection mediated by the 50% thymine-capped PAMAM dendrimer/pDNA complex (17). Thus, 50% thymine-capped PAMAM dendrimers were used to form the dendrimer/siRNA/pDNA complex at a weight ratio of approximately 2:1:1.…”
Section: Preparation and Characterization Of Tumor-targeted Lipid/ De...supporting
confidence: 92%
“…First, this dendrimer condenses the genetic cargoes (siRNA and pDNA) and increases the stability of the nanoscale nucleic acid-dendrimer-CaP cores. Thymines and primary amines on the thymine-capped dendrimer may synergistically interact with and protect siRNA/ pDNA via electrostatic interaction and hydrogen bonding (17). Second, the dendrimer triggers efficient endosomal escape and intracellular release of genetic cargoes (24), increases pDNA uptake in the nucleus, and induces strong transfection activity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Xu et al (2019) demonstrated that grafting PAMAM dendrimers with guanidinobenzoic acid enhanced binding and endosomal disruption, enabling efficient delivery of various proteins and peptides into the cytosol of living cells. Furthermore, a recent study found that modification of PAMAM dendrimers (i.e., by capping the dendrimers with thymine) can result in several multifunctional immunotherapy characteristics: (1) synergistic interaction with and protection of genetic cargoes (siRNA and pDNA) via electrostatic interaction and hydrogen bonding; (2) enhanced endosomal escape and intracellular release of genetic cargoes; (3) increased pDNA uptake in the nucleus and enhanced gene transfection activity; and (4) enhanced stimulation of prominent immunity-related pathways and promotion of cellular immunity (K.-W. Huang et al, 2020;Yan et al, 2015). However, although many of the PAMAM dendrimerbased vaccines have demonstrated high efficiency and selectivity, their effects are often ephemeral, requiring additional research to be completed to develop nanovaccines with long-term anti-tumor immunity.…”
Section: Vaccinesmentioning
confidence: 99%
“…Specifically for the dendrimer-based vaccine systems, many of the systems developed so far have not yet been optimized for introduction into clinical settings. Several studies have shown that the tested systems were not sufficient to protect individuals from subsequent challenges and only induced ephemeral immunity effects (Daftarian et al, 2011;K.-W. Huang et al, 2020;Yan et al, 2015). Also, regardless of the type of dendrimer, the scaffolds had to undergo additional conjugation with functional groups or be paired with checkpoint inhibitors to ensure successful cancer inhibition (Blankenstein et al, 2012;Horvath et al, 2002;Kumar et al, 1992;Vichier-guerre et al, 2000;Xu et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%